Age matters: The effect of onset age of video game play on task-switching abilities - Hartanto, A.; Xing Toh, W.; Yang, H. (Attention, Perception, & Psychophysics, 2016)
Although prior research suggests that playing video games can improve cognitive abilities, recent empirical studies cast doubt on such findings (Unsworth et al., 2015). To reconcile these inconsistent findings, we focused on the link between video games and task switching. Furthermore, we conceptualized video-game expertise as the onset age of active video-game play rather than the frequency of recent gameplay, as it captures both how long a person has played video games and whether the individual began playing during periods of high cognitive plasticity. We found that the age of active onset better predicted switch and mixing costs than did frequency of recent gameplay; specifically, players who commenced playing video games at an earlier age reaped greater benefits in terms of task switching than did those who started at a later age. Moreover, improving switch costs required a more extensive period of video-game experience than did mixing costs; this finding suggests that certain cognitive abilities benefit from different amounts of video game experience.